Europeanization through cross-border cooperation: the case of western Ukrainian regions - Volkova, Iryna (2019)
Ukraine acquires many benefits from its proximity to the European Union (EU), such as the possibility to be included in many strategies and programmes, namely in the Cross-border Programmes. This type of cooperation, which is used as a mechanism of horizontal governance, creates opportunities to work in joint programmes and to increase the engagement of Civil Society Organizations (CSO) in the peripheral regions of Ukraine. Also, the close engagement between partners of the European member states and Ukraine can be used as a tool for diffusion of Europeanization. In this dissertation, we will use Cross-Border cooperation in the western regions of Ukraine as a case study to show the mechanisms of diffusion of Europeanization through the horizontal mode of governance. Cross-Border Cooperation in Ukraine and its contribution to Europeanization is examined on the basis of evaluation reports, which present the concluded objectives, implications, and surveys on the opinions of the beneficiaries involved in the Programmes. In essence, in this work we intended to complement the study of Cross-Border Cooperation of the EU with external countries, and to complement the study on Ukraine’s relation with the EU, and its Europeanization. The research suggests that, even if the CBC is an instrument of Europeanization, its contribution is minimal and will only be seen in the long run, and it has almost no impact on legislation and institutions in Ukraine.